Unveiling STEM Education Conceptions: Insights from Pre-Service Mathematics and Science Teachers - Laksono, Pandu Jati; Suhadi, Suhadi; Efriani, Arvin (Integrated Science Education Journal, 2025)
Purpose of the study: This study aims to analyze STEM education conceptions among pre-service mathematics and science teachers, focusing on their perceptions, understanding, and readiness to implement STEM education. The research seeks to identify gaps in STEM comprehension to inform teacher preparation program development. Methodology: This descriptive quantitative study describes the STEM concept among prospective science and mathematics teachers using an online questionnaire with Likert scale and open-ended questions. Data were analyzed using descriptive statistics, such as mean and standard deviation, and validated with Gregory's content validity formula, and Cronbach's alpha. Main Findings: Main findings indicate that 14.58% of respondents demonstrated very high STEM conception with scores exceeding 112.37, while 31.25% exhibited high conception within the range of 98.83 to 112.37. Conversely, 41.67% showed low conception with scores between 85.33 and 98.82, and 12.50% had very low conception, scoring below 85.33. Overall, only 45.83% of pre service teachers possessed adequate STEM conception, highlighting that 54.17% require strengthening in their understanding of STEM. Mathematics is seen as an essential foundational element in STEM education, with technology integration being key to improving learning outcomes. This study highlights the need for curriculum revision and professional development to improve STEM readiness among preservice teachers. Novelty/Originality of this study: This study identified a lack of STEM concepts among preservice mathematics and science teachers, and highlighted the urgency of revising the curriculum with an interdisciplinary approach that connects theory and practice. Limitations include self-reported data and a limited focus, so a larger study is needed.